Production and quality of melons grown in two different substrates under soilless cultivation - Cecilio Filho, A. B. [UNESP]; May, A. [UNESP]; Branco, R. B F [UNESP]; Braz, L. T. [UNESP]; Peixoto, J. R. (My University, 2003)
This investigation was conducted at UNESP, Jaboticabal campus, São Paulo, Brazil, from March 8 to June 21, 1999, to evaluate net melon yield and fruit quality, using soilless culture. 'Bônus 2' and 'Mission' cultivars were grown in a substrate of ground quartz or thick sand, in a randomized block experimental design. Leaf and stem dry matter production, leaf size and soluble solids content of the fruit, of 'Bônus 2' were superior to 'Mission'. There was a significant interaction for the evaluated characteristics of fruit dry mass production and yield. The largest accumulation of fruit dry mass and yield of the 'Bônus 2' cultivar (61,325 kg/ha) was observed when a substrate of ground quartz was used, while the yield for the 'Mission' cultivar was higher in a substrate of thick sand (42,125 kg/ha).
Keywords: Cucumis melo; Cultivar; Net melon; Protected cultivation; Substrate; Yield